Effectiveness of Integrative Therapy for Parkinson’s Disease Management - Woo, Yeonju; Hyun, Min Kyung (Frontiers in Aging Neuroscience, 2019)
OBJECTIVES: To investigate the effectiveness of integrative therapy on prevalence and length of hospitalization and management of major complications of Parkinson's Disease (PD) in the Republic of Korea. METHODS: This study was a retrospective cohort analysis conducted using the National Health Insurance Service-National Sample Cohort in the Republic of Korea. Patients over 65 years old who were newly diagnosed with PD during 2007–2011 were identified. The integrative therapy group was defined as patients treated with both Korean medicine (KM) and biomedicine, and the monotherapy group consisted of patients treated with biomedicine alone. From PD diagnosis to 2013, the prevalence and annual length of hospitalization because of PD and major complications (dementia, depression and pneumonia/sepsis) were analyzed using logistic regression, ANOVA and t-tests after propensity score (PS) matching with a 1:1 ratio. RESULTS: After PS estimation and matching, the cohort used in the analysis included 228 subjects (114 integrative therapy group, 114 monotherapy group). Sex, age, index year, comorbidity, severity of disability, neurologic care and anti-parkinsonism medication (levodopa, ropinirole, pramipexole, selegiline) were adjusted in both groups. The prevalence of hospitalization due to pneumonia/sepsis was 0.50 times (95% C.I: 0.26–0.96) lower in the integrative therapy group than the monotherapy group, which was statistically significant (p=0.038). The prevalence and annual length of total hospitalization and hospitalization because of PD, dementia, and depression in the integrative therapy group showed positive results compared to the monotherapy group, but these differences were not statistically significant. CONCLUSIONS: It has not been clearly identified that integrative therapy with KM and biomedicine for PD management is better treatment for patients compared to biomedicine monotherapy; however, we found a clue of better result in integrated therapy. Therefore, further investigation by increasing the number of subjects is needed to confirm the findings presented herein.